Developmental and digestive flexibilities in the midgut of a polyphagous pest, the cotton bollworm, helicoverpa armigera - Sarate, P. J.; Tamhane, V. A.; Kotkar, H. M.; Ratnakaran, N.; Susan, N.; Gupta, Vidya S.; Giri, Ashok P. (Journal of Insect Science, 2012)
Developmental patterns and survival of the cotton bollworm, Helicoverpa armigera Hubner (Lepidoptera: Noctuidae), a polyphagous insect pest, have been studied with reference to the effect of diet on major gut digestive enzymes (amylases, proteases, and lipases). Significant correlations between nutritional quality of the diet and larval and pupal mass were observed when H. armigera larvae were fed on various host plants viz. legumes (chickpea and pigeonpea), vegetables (tomato and okra), flowers (rose and marigold), and cereals (sorghum and maize). Larvae fed on diets rich in proteins and/or carbohydrates (pigeonpea, chickpea, maize, and sorghum) showed higher larval mass and developed more rapidly than larvae fed on diets with low protein and carbohydrate content (rose, marigold, okra, and tomato). Low calorific value diets like rose and marigold resulted in higher mortality (25-35%) of H. armigera. Even with highly varying development efficiency and larval/pupal survival rates, H. armigera populations feeding on different diets completed their life cycles. Digestive enzymes of H. armigera displayed variable expression levels and were found to be regulated on the basis of macromolecular composition of the diet. Post-ingestive adaptations operating at the gut level, in the form of controlled release of digestive enzymes, might be a key factor contributing to the physiological plasticity in H. armigera.
Keywords: amylases; larval performance; Lipases; Proteases